2019
DOI: 10.3390/nu11112785
|View full text |Cite
|
Sign up to set email alerts
|

Fat Addiction: Psychological and Physiological Trajectory

Abstract: Obesity has become a major public health concern worldwide due to its high social and economic burden, caused by its related comorbidities, impacting physical and mental health. Dietary fat is an important source of energy along with its rewarding and reinforcing properties. The nutritional recommendations for dietary fat vary from one country to another; however, the dietary reference intake (DRI) recommends not consuming more than 35% of total calories as fat. Food rich in fat is hyperpalatable, and is liabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 107 publications
0
24
1
1
Order By: Relevance
“…Before going into detail, we would like to emphasize that a reduced oro-sensory perception would trigger high consumption of palatable food, thus either leading to obesity or worsening this pathology [67,68], though we should not ignore the implication of the food addiction component, particularly for sweet food and those rich in fat [69,70]. The studies conducted on healthy and obese participants suggested that the latter group exhibited lower sensitivity than the former for sweet and sour taste [71].…”
Section: Obesity and Reduced Ons Perceptionmentioning
confidence: 99%
“…Before going into detail, we would like to emphasize that a reduced oro-sensory perception would trigger high consumption of palatable food, thus either leading to obesity or worsening this pathology [67,68], though we should not ignore the implication of the food addiction component, particularly for sweet food and those rich in fat [69,70]. The studies conducted on healthy and obese participants suggested that the latter group exhibited lower sensitivity than the former for sweet and sour taste [71].…”
Section: Obesity and Reduced Ons Perceptionmentioning
confidence: 99%
“…In university students, symptoms of FA were in majority related to combined high-fat savory and high-fat sweet foods, and rarely for mainly sugar-containing food [ 2 ]. Concerning fat, which has its own metabolic, physiological, and nutritional profiles, human evidence is scarce and comes mostly from studies on FA: individuals with FA had higher dietary fat intake compared to those without FA; animal models suggested that fat addiction may have different mechanisms to sugar addiction [ 44 ]. Highly processed foods, with the addition of fat and/or refined carbohydrates (sugar, white flour), have drawn the most attention.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have attempted to parse out the psychological and physiological etiology of food addiction. This review article by Sarkar et al [7] examines the specific role of dietary fats in compulsive overeating. They review preclinical, psychological and clinical evidence to argue for the addiction to fat rich diets as a prominent subset of food addiction.…”
Section: Fat Addiction: Psychological and Physiological Trajectorymentioning
confidence: 99%